Legendre Invariance and Geometrothermodynamics Description of the 3D Charged-Dilaton Black Hole - Yiwen Han; XiaoXiong Zeng (Advances in High Energy Physics)
We first review Weinhold information geometry and Ruppeiner information geometry of 3D charged-dilaton black hole. Then, we use the Legendre invariant to introduce a 2-dimensional thermodynamic metric in the space of equilibrium states, which becomes singular at those points. According to the analysis of the heat capacities, these points are the places where phase transitions occur. This result is valid for the black hole, therefore, provides a geometrothermodynamics description of black hole phase transitions in terms of curvature singularities.